Enhanced Biocide Treatments with D-amino Acid Mixtures against a Biofilm Consortium from a Water Cooling Tower - Jia, Ru; Li, Yingchao; Al-Mahamedh, Hussain H.; Gu, Tingyue (Frontiers in Microbiology, 2017)
Different species of microbes form biofilms in cooling water systems. They lead to microbiologically influenced corrosion (MIC) and biofouling that increase the operational and maintenance costs of the system. In this work, two D-amino acid mixtures enhanced two non-oxidizing biocides (tetrakis hydroxymethyl phosphonium sulfate (THPS) and NALCO 7330 (isothiazoline derivatives) and one oxidizing biocide (bleach (NaClO)) against a biofilm consortium from a water cooling tower in lab testing. Fifty ppm (w/w) D8 (an equimass mixture of D-methionine, D-leucine, D-tyrosine, D-tryptophan, D-serine, D-threonine, D-phenylalanine, and D-valine) enhanced 15 ppm THPS and 15 ppm NALCO 7330 by achieving similar efficacies compared with the 30 ppm THPS alone treatment and the 30 ppm NALCO 7330 alone treatment, respectively in the one-batch 3-hour biofilm removal test. A sequential treatment method was used to enhance bleach because D-amino acids react with bleach. After a 4-hour biofilm removal test, the sequential treatment of 5 ppm bleach followed by 50 ppm D8 achieved extra 1-log reduction of acid producing bacteria, sulfate reducing bacteria, and general heterotrophic bacteria sessile cell counts compared with the 5 ppm bleach alone treatment. The 10 ppm bleach alone treatment showed similar efficacy with the sequential treatment of 5 ppm bleach followed by 50 ppm D8. The efficacy of D8 was better than D4 (an equimass mixture of D-methionine, D-leucine, D-tyrosine, and D-tryptophan) to enhance these biocides against the consortium.